Antioxidant and Anti-Infl ammatory Activities of Ginger Aqueous and Ethanolic Extracts - A, Sellal; R, Belattar; A, Senator (Pharmacognosy Communications)
In the present study, the activities of ethanolic and aqueous extracts from ginger rhizome were evaluated in vivo using acetic acid induced vascular permeability and xylene induced ear edema by topical application in mice as a model of acute infl ammation. The oral administration of this extracts at dose of 400 mg/kg one hour before the induction of infl ammation showed a highly signifi cant (p ≤ 0.01) anti-infl ammatory effect (compared to control group considered as 100% of infl ammation). The antioxidant effect of the ethanolic extract was also studied in vitro using the DPPH free radical scavenging assay, total antioxidant activity, metal chelating activity and ß-carotene/linoleic acid tests. Where the increased volumes of extract studied taken from a stock solution of a fi xed concentration 1 mg/ml at 25–250 μl in the DPPH free radical scavenging assay, 15 μl in the total antioxidant activity assay and 250 μl in the ß-carotene / linoleic acid test gave a signifi cant (p ≤ 0.01) antioxidant activity. The results obtained showed that this extract has a good scavenger effect towards DPPH radical, and the lipid peroxidation activity in the total antioxidant activity assay and ß-carotene/linoleic acid tests. In Contrast, this extract had no metal chelating effect where the volumes of 25–200 μl gave a non signifi cant differences.
Keywords: Infl ammation; oxidation; free radicals; ginger; Zingiber offi cinale; DPPH